2019
DOI: 10.1002/anie.201909177
|View full text |Cite
|
Sign up to set email alerts
|

1‐Picolinyl‐5‐azido Thiosialosides: Versatile Donors for the Stereoselective Construction of Sialyl Linkages

Abstract: With the picolinyl (Pic) group as a C‐1 located directing group and N3 as versatile precursor for C5‐NH2, a novel 1‐Pic‐5‐N3 thiosialyl donor was designed and synthesized, based on which a new sialylation protocol was established. In comparison to conventional sialylation methods, the new protocol exhibited obvious advantages, including excellent α‐stereoselectivity in the absence of a solvent effect, broad substrate scope encompassing the challenging sialyl 8‐ and 9‐hydroxy groups of sialic acid acceptors, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…reported a C1‐picolinyl donor that favored the formation of the α‐anomer in the glycosylation of the C6 hydroxyl of Gal acceptor 17 (Scheme 10). [37] High α‐selectivity was also observed for the glycosylation of the C3 hydroxyl of Gal 35 (42 %, α only). They demonstrated that the protonated picolinyl group stabilizes the β‐sialyl triflate, which then undergoes S N 2‐like substitution to provide α‐sialosides.…”
Section: Synthesis Of α‐Sialosidesmentioning
confidence: 94%
See 1 more Smart Citation
“…reported a C1‐picolinyl donor that favored the formation of the α‐anomer in the glycosylation of the C6 hydroxyl of Gal acceptor 17 (Scheme 10). [37] High α‐selectivity was also observed for the glycosylation of the C3 hydroxyl of Gal 35 (42 %, α only). They demonstrated that the protonated picolinyl group stabilizes the β‐sialyl triflate, which then undergoes S N 2‐like substitution to provide α‐sialosides.…”
Section: Synthesis Of α‐Sialosidesmentioning
confidence: 94%
“…[31,36] Sun et al introduced a picolinyl group as a C1 auxiliary. [37] Compared with the general C1-methyl ester derivative, the (2-methylthio)ethyl derivative 25 showed significantly higher α-selectivity in primary alcohol glycosylation. [35] The use of dimethoxyethane (DME) as a solvent enhanced α-selectivity (α : β = 95 : 5) compared to the cases of MeCN (α : β = 80 : 20) and CH 2 Cl 2 (α : β = 68 : 32).…”
Section: C1-modified Sialyl Donorsmentioning
confidence: 97%
“…The versatility and exclusive stereoselectivity of the above-mentioned approach paved the way to the efficient synthesis of N-glycan antennae (type I and II) in combination with the MPEP glycosylation protocol using a "latent-active" strategy (Scheme 31). [49] This synthesis involved the coupling of picolinyl group containing donor 112 and primary acceptor 115 upon activation of NIS/TfOH to give stereoselective disaccharide sialoside 116 in 90% yield and then undergo several reaction steps to ultimately delivered type I antennae. However, the synthesis of type II antenna 124 was even more challenging and involved an eight-steps longest linear sequences starting with common picolinyl protected donor 112 as well as diol acceptor 121.…”
Section: Sialyl Donorsmentioning
confidence: 99%
“…Thereafter Jian‐Song Sun and group (2019) [49] utilized the efficacy of the picolinyl group to design and prepared the versatile 1‐Pic‐5‐N 3 sialyl donor. To elaborate the act of the Pic group they used two types of donors ( 111 and 112 ) and performed their glycosylation with several acceptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation